2002
DOI: 10.1038/sj.gene.6363879
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of classical human low-affinity Fcγ receptor genes

Abstract: The classical low-affinity Fc␥ receptor genes (Fc␥RIIA, B, C and Fc␥RIIIA, B)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 47 publications
3
66
0
Order By: Relevance
“…Perhaps these results reflect some linkage disequilibrium between the FcgRIIIA and FcgRIIC genes, as they are in close proximity to one other in the genome. 35 36 and RF can stimulate cytokine release from these cells. 37 More recently, the synovial tissue expression of IL-15 was observed.…”
Section: Fccriiia Allelic Polymorphisms In Ramentioning
confidence: 99%
“…Perhaps these results reflect some linkage disequilibrium between the FcgRIIIA and FcgRIIC genes, as they are in close proximity to one other in the genome. 35 36 and RF can stimulate cytokine release from these cells. 37 More recently, the synovial tissue expression of IL-15 was observed.…”
Section: Fccriiia Allelic Polymorphisms In Ramentioning
confidence: 99%
“…1). This low-affinity receptor family comprises three class II genes (FCGR2A, FCGR2B, FCGR2C) and two class III genes (FCGR3A, FCGR3B) [24]. Functionally, the gene products, FcgRs, mediate immune responses by binding specifically to the Fc portion of immunoglobulin G molecules.…”
mentioning
confidence: 99%
“…Other than collagen, OPN is the major extracellular matrix protein in bone, and it has been shown to act as an activator in osteoclasts (1). OPN also works as a Th1 cytokine (2,3). Rheumatoid arthritis (RA) is a typical bone resorption inflammatory disease, the pathogenesis of which is thought to stem from Th1 hyperactivation (4).…”
mentioning
confidence: 99%
“…However, considering the limitations in studies using knockout mice and previous reports on OPN as a cytokine and a factor in osteoclast activation (1,2,9) 3B (1,3). Linkage of the chromosomal region encompassing FCGR loci with systemic lupus erythematosus (SLE) has been observed (4)(5)(6), and numerous studies have demonstrated association of 1 or more of the FCGR alleles with SLE (1).…”
mentioning
confidence: 99%